Measurement and evaluation of the hydraulic properties of horticultural substrates. Issue 6 (2nd June 2016) - Schindler, Uwe; Müller, Lothar; Eulenstein, Frank
Abstract: Sustainable, environmentally friendly and resource-saving water and nutrient management in horticulture requires knowledge of the suitability of horticultural substrates for each specific application. One specific element is their hydraulic performance. To meet this requirement, methods are needed (1) to measure the hydraulic properties and (2) to evaluate the hydraulic quality of the horticultural substrates. The aim of this study was (1) to test the extended evaporation method and the HYPROP systems for quantifying the substrate's hydraulic properties (the water retention curve, the unsaturated hydraulic conductivity function, the shrinkage dynamics, the bulk density), and (2) to develop a rating framework for assessing the hydraulic suitability of the substrates. The hydraulic evaluation was split into cultivation under free drainage in the ground and cultivation in containers. The hydraulic criteria related to high-quality horticultural substrates were defined as the amount of easily plant-available water, the air capacity and the height of capillary rise. Limiting factors could be water repellency effects and shrinkage. The rating framework consists of five classes between non-satisfactory and very good. It was tested on 23 commercial horticultural substrates. Both the measurement methods for quantifying soil hydraulic properties and the evaluation procedure proved applicable.